2012
DOI: 10.5539/mas.v6n11p20
|View full text |Cite
|
Sign up to set email alerts
|

Murthy’s Estimator in Unequal Probability Inverse Adaptive Cluster Sampling

Abstract: This paper derives a Murthy's unbiased estimator of population total under unequal probability inverse sampling. A general unequal probability inverse sampling is combined with adaptive cluster sampling. An unbiased estimator of population total and its variance estimator are given using Murthy's approach. The general unequal probability inverse adaptive cluster sampling and general equal probability inverse adaptive cluster sampling are compared using simulation study based on real life data. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…, we also recommend the unbiased estimator. For future studies, we can consider applying the ratio estimator in adaptive sampling schemes as suggested by Thompson (1990) and Sangngam (2013) for.…”
Section: Discussionmentioning
confidence: 99%
“…, we also recommend the unbiased estimator. For future studies, we can consider applying the ratio estimator in adaptive sampling schemes as suggested by Thompson (1990) and Sangngam (2013) for.…”
Section: Discussionmentioning
confidence: 99%
“…Sangngam () introduced an unbiased estimator of τ for use in an unequal probability inverse sampling design given bytrueτ^S=Nfalse(truep^y¯c+(1pfalse^)y¯c¯false),where pfalse^=false(m1false)/false(n01false), trueyfalse¯c=1miScyi*/pi* and trueyfalse¯truecfalse¯=1n0miStruecfalse¯yi*/pi*. The quantities yi* and pi* are the sum of the y and selection probability values of units belonging to network i , respectively. The number of units selected sequentially which are required to obtain m rare units before adding neighbouring units is ns.…”
Section: Estimatorsmentioning
confidence: 99%
“…Inverse sampling with unequal selection probabilities (and with replacement) was introduced by Greco & Naddeo (). Sangngam () introduced an unbiased estimator for use with unequal probability inverse sampling designs, where initial units are selected with replacement. In such sampling designs, the number of distinct rare units may be smaller than the predetermined number of rare units because sampling is with replacement.…”
Section: Introductionmentioning
confidence: 99%
“…They believed that the method could be applied at a national level. Also, Sangngam () incorporated unequal probability inverse sampling with adaptive cluster sampling where the probabilities were computed based on an auxiliary variable. He evaluated his design using the ring‐necked duck data (Smith, Conroy, & Brakhage, ) and showed the proposed strategy was efficient with a highly correlated auxiliary variable.…”
Section: Introductionmentioning
confidence: 99%